Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

? asked in Science & MathematicsMathematics · 1 decade ago

very hard math question, well to me?

can anybody solve this hard math question

3 to the 8th power times 6 to the fifth power over 3 to the 10 power times 6 to the third power

the answer choices are 4,2,8,6

im not cheating because its a interim and the teacher gave it back to redo them to study

13 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    (3^8)*(6^5)

    ___________

    (3^10)*(6^3)

    = 3^(8 - 10)*6^(5 - 3)

    = 3^(-2)*6^2

    = (6^2) / (3^2)

    = 36 / 9

    = 4

  • Tomp
    Lv 7
    1 decade ago

    When you multiply like values you add the exponents. Similarly, when dividing, you subtract exponents.

    For example, suppose you want to multiply a^5 times a^3 (the '^n' notation means 'to the power of n)

    a^5 x a^3 = (a x a x a x a x a ) x (a x a x a)

    = a x a x a x a x a x a x a x a

    = a^8

    Also a^5 divided by a^3 = (a x a x a x a x a ) / (a x a x a)

    = (a x a) x (a x a x a) /(a x a x a)

    = (a x a) x 1

    = (a x a)

    = a^2

    Furthermore, since a^0 = 1 for all numbers a

    1/a = a^0 / a^1

    = a^(0-1)

    = a^(-1)

    Similarly, for any power k

    1/a^k = a^(-k)

    So we could have

    (a x a x a x a x a ) / (a x a x a)

    = a^5 x a (-3)

    = a^(5-3)

    = a^2

    One more point: if a = mn (understood to mean m x n), then

    a^k = (mn)^k = m^k x n^k

    So, armed with this knowledge and knowing that 6 equals 3 x 2, your problem

    3 to the 8th power times 6 to the fifth power over 3 to the 10 power times 6 to the third power

    becomes

    (3^8 x 6^5) / (3^10 x 6^3) = (3^8 x (3 x 2)^5) / (3^10 x (3 x 2)^3)

    = (3^8 x 3^5 x 2^5) / (3^10 x 3^3 x 2^3)

    = (3^(8+5) x 2^5) / (3^(10+3) x 2^3)

    = (3^13 x 2^5) / (3^13 x 2^3)

    = 3^13 x 2^5 x 3^(-13) x 2(-3)

    = 3^(13-13) x 2^(5-3)

    = 3^0 x 2^2

    = 1 x 2^2

    = 1 x 4

    = 4

    It's a bit drawn out, but it's better that you know how to solve such problems rather than simply giving you the answer.

    It's not particularly difficult; it's just a matter of knowing the mechanics of operating on exponents. Once you get the idea (as demonstrated above), it will be a breeze!

  • 1 decade ago

    Answer = 4

    Use a calculator or simplify the following

    (3^8 x 6^5) / (3^10 *6^3) = (3^[8-10]) x (6^[5-3]) = 3^(-2) x 6^2 = [1/3^2] x 6^2

    = 1/9 x 6 x 6

    = 36/9

    =4

  • 1 decade ago

    4

  • 1 decade ago

    (3^8)(6^5)/((3^10)(6^3))

    When dividing with a common base, subtract the exponents to get:

    (3^(8-10)) (6^(5-3))

    which simplifies to:

    3^-2 * 6^2

    negative exponents mean: a^-n = 1/a^n, so 3^-2=1/3^2 which is 1/9

    6^2 = 36 so:

    36 (1/9) =4

    So the answer is 4

  • ?
    Lv 7
    1 decade ago

    3^8*6^5/(3^10*6^3) =

    4

  • Ray S
    Lv 7
    1 decade ago

    ____________________________

      3⁸6⁵           6⁵⁻³              6²

    ——– = ——– = —— = (6 ̸ 3)² = 2² = 4

     3¹⁰6³         3¹⁰⁻⁸           3²

    ___________________________________

  • ?
    Lv 7
    1 decade ago

    (3^8 * 6^5) / (3^10 * 6^3) = 6^2 / 3^2 = 36/9 = 4

  • SPB
    Lv 6
    1 decade ago

    3^8 * 6^5 / 3^10 * 6^3

    simplify

    33333333 * 66666 / 3333333333 * 666 cancel out the 3's and 6's to get

    66 / 33 or

    6^2/3^2 = 36/9 = 4

  • HPV
    Lv 7
    1 decade ago

    (3^8 x 6^5 ) / (3^10 x 6^3) = (3^8 / 3^10) x (6^5 / 6^3) = (3^-2)(6^2) = (1 / 3^2)(6^2) = (1/9)(36) = 4

Still have questions? Get your answers by asking now.